Exploring the space of conviviality with newcomers and host communities - Luraschi, Silvia (Adult Education Discourses, 2022)
This paper explores the space of conviviality between newcomers and host communities exemplifying the author’s way as a researcher to be at the same time an activist in Italy. The author investigates her position as an adult educator and researcher to focus on how the informal process of research on adult education has a ‘transformative’ effect at the meso (social) level dimension of interaction. Group experience is life experience and food is one of the most powerful connective tools humans have: it stimulates all of the senses, evokes deep memories and connects one with the wider system of interaction and complexity. In this meso-level dimension newcomers and native citizens interconnected their senses through sharing food. The paper includes different languages and styles: autoethnographic field notes of informal conversations between migrants and Italians involved in the research, transcriptions of dialogues and correspondence with research participants and photos taken during the field of research. All texts and images are analyzed to imagine new forms of embodied research in adult education.